Compositional Thought and Musical Structure in Joyce’s Works - Pastor Comín, Juan José (Estudios Ingleses de la Universidad Complutense, 2009)
Scholars have catalogued literally thousands of musical allusions — to singers, composers, instruments, musical venues and, of course, songs of various stripes — many of them integral to the understanding of his poems, stories, and novels. Joyce’s books are saturated with a deep affection for music with which he grew up and which stayed with him all his life. Joyce enjoyed giving literary interpretations of the contrapuntal techniques in music. This turned into a kind of intellectual exercise in which he professed to use the devices for his own purposes in his own medium. This article proposes a bibliographical revision and studies how significant are different systems of coetaneous musical composition to right understand the structure and architecture of his works.